PERDAGANGAN MASA PRASEJARAH DI PAPUA (TINJAUAN BERDASARKAN TINGGALAN ARKEOLOGI) - Erlin Novita Idje Djami (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
Prehistoric trade in Papua characterized by the existence of material culture beyond the diffusion of cultural products such as pottery, stone axes, bronze axes, nekara bronxe and beads of Indo-Pacific found in several sites in the territory of Papua. The existence of those cultural objects is indicated as a result of longdistance trade activities and is supported by progress in the field of maritime. In addition to long-distance trade, there was also a local trade proved by the existence of shells of shellfish in inland areas and there was even one species of molluscs gastropods class family cypraea moneta that was used as currency (mege/ siwol/tinale) by rural communities, particularly Ekagi, Ngalum and Timorini ethnic in the central Papua. Related to trade, there was not only merchandise but also production and distribution of goods and trade processes which occurred with reference to the trade proces in traditional societies of Papua